INVOLVEMENT OF OPIOIDERGIC, TRYPTAMINERGIC AND K+ ATP CHANNELS IN THE ANTINOCICEPTIVE ACTION OF INDAZOLE AND ITS DERIVATIVES - CHAKRAPANI CHEEKAVOLU,; M MUNIAPPAN,; SIMHADRI V.S.D.N.A. NAGESH, (International Journal of Pharma and Bio Sciences, 2016)
The present study was designed to investigate the anti-nociceptive action of indazole, 5 – aminoindazole and 6 – nitroindazole and the possible mechanisms involved in this effect. The anti - nociceptive effect was studied using three different nociceptive assays. These are acetic acid assay, formalin induced nociception and hot plate methods. Swiss albino mice were selected for this study. The participation of opioid, tryptaminergic, dopaminergic and K+ ATP channels in the anti-nociceptive effect were also studied by using appropriate interacting agents. Indazole and its derivatives exhibited a significant dose dependent inhibition of acetic acid writhing. The paw licking response time was reduced in formalin induced nociception in a dose dependent manner by indazole and its derivatives. A significant increase in withdrawal latency time was also observed in thermal nociception after indazoles treatment. These observations revealed the anti-nociceptive effect of indazole and its derivatives. The participation of opioid system and K+ ATP channel was identified in the anti - nociceptive effect of indazole and its derivatives. Additionally, participation of tryptaminergic 5 - HT3 receptors could also be recorded in the anti-nociceptive action of 6 – nitroindazole, but not in other investigated compounds. Pretreatment with haloperidol, a non specific dopamine receptor antagonist potentiated the anti - nociceptive response of indazole and its derivatives. The present study identified the anti - nociceptive effect of indazole and its derivatives in mice and mechanisms involved in the anti - nociceptive activity of these compounds.